2016
DOI: 10.3389/fpls.2016.01470
|View full text |Cite
|
Sign up to set email alerts
|

Charophytes: Evolutionary Giants and Emerging Model Organisms

Abstract: Charophytes are the group of green algae whose ancestral lineage gave rise to land plants in what resulted in a profoundly transformative event in the natural history of the planet. Extant charophytes exhibit many features that are similar to those found in land plants and their relatively simple phenotypes make them efficacious organisms for the study of many fundamental biological phenomena. Several taxa including Micrasterias, Penium, Chara, and Coleochaete are valuable model organisms for the study of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 99 publications
0
30
0
2
Order By: Relevance
“…As many plant GAPs are encoded by gene families that are taxonomically conserved, neo‐functionalization likely occurred early in the evolutionary history of green plants. An intriguing area for future study is the biology of GAPs in early diverging lineages of green plants, such as the charophycean green algae (Domozych et al ).…”
Section: Discussionmentioning
confidence: 99%
“…As many plant GAPs are encoded by gene families that are taxonomically conserved, neo‐functionalization likely occurred early in the evolutionary history of green plants. An intriguing area for future study is the biology of GAPs in early diverging lineages of green plants, such as the charophycean green algae (Domozych et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In ancient times, charophytes dominated the submerged vegetation in shallow freshwater and probably many brackish water ecosystems. Since the angiosperms showed up on the "stage" around 200-250 million years ago (Morris et al 2018), however, interactions with these "newcomers" have been one of the most important issues in the life of the phylogenetically far older (Domozych et al 2016) charophytes.…”
Section: Nasty Neighbours and Fancy Friendsinteractions Between Charomentioning
confidence: 99%
“…Phylogenetic analysis has suggested that all land plants—from bryophytes to angiosperms—share a common aquatic plant ancestor, most likely an alga closely related to charophytes. [ 30 ] Throughout their evolution, plants have been involved in close interactions with microbes, and land plants are believed to have arisen as a result of an ancient symbiosis between an alga and an aquatic fungus. [ 31 ] The first land plant to emerge is considered to have been a liverwort‐like species.…”
Section: How Have Flavonoid Functions Evolved In Land Plants?mentioning
confidence: 99%